2007
DOI: 10.1002/ajp.20461
|View full text |Cite
|
Sign up to set email alerts
|

Circadian cortisol secretion and circadian adrenal responses to ACTH are maintained in dexamethasone suppressed capuchin monkeys (Cebus apella)

Abstract: We tested the hypothesis that the capuchin monkey adrenal (Cebus apella) gland has oscillatory properties that are independent of adrenocorticotropic hormone (ACTH) by exploring under ACTH suppression by dexamethasone: (i) maintenance of a circadian rhythm of plasma cortisol and (ii) clock time dependency of plasma cortisol response to exogenous ACTH. The capuchin monkey had a clear ACTH and plasma cortisol rhythm. Dexamethasone treatment resulted in low non-rhythmic ACTH levels and decreased cortisol to 1/10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
21
0
5
Order By: Relevance
“…We found results regarding GCM diurnal variation similar to those obtained by field and laboratory studies (e.g Kriegsfeld & Silver, 2006;Torres-Farfan et al, 2008) and we obtained significant results about the influence of different factors over individuals' GCM levels depending on their age/sex classes. Specifically, the variation of GCM levels of immature animals was associated with decreased fruit intake; the GCM levels of adult males increased mostly during the breeding season; and the variation of GCM levels in adult females might be explained by the increased energy demand during the late stage of pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…We found results regarding GCM diurnal variation similar to those obtained by field and laboratory studies (e.g Kriegsfeld & Silver, 2006;Torres-Farfan et al, 2008) and we obtained significant results about the influence of different factors over individuals' GCM levels depending on their age/sex classes. Specifically, the variation of GCM levels of immature animals was associated with decreased fruit intake; the GCM levels of adult males increased mostly during the breeding season; and the variation of GCM levels in adult females might be explained by the increased energy demand during the late stage of pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…It is well established that the circadian production of glucocorticoids involves the orchestrated action of the circadian rhythm of ACTH, adrenal innervation, and local adrenal factors (1)(2)(3)(4). However, there is evidence suggesting the involvement of additional regulatory factors that may include the neurohormone melatonin and an intrinsic adrenal clock (5,6).…”
mentioning
confidence: 99%
“…However, there is evidence suggesting the involvement of additional regulatory factors that may include the neurohormone melatonin and an intrinsic adrenal clock (5,6). The capuchin monkey has a clear ACTH and plasma cortisol rhythm (4) showing maximal values in the early morning as in other diurnal nonhuman primates and the human (7)(8)(9). Recently we showed that in vivo suppression of ACTH by dexamethasone decreased cortisol production to one tenth but did not abolish a circadian rhythm of plasma cortisol in the capuchin, similar to findings in the rat (2,4).…”
mentioning
confidence: 99%
“…A fixed time was chosen for collection because cortisol levels in primates fluctuate daily [16,17]. Fecal samples were collected from all six animals before and after removal, and were only collected when the producer could be identified; zoo staff helped with this process.…”
Section: Fecal Sample Collectionmentioning
confidence: 99%